2014
DOI: 10.1073/pnas.1404399111
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin receptor TrkB promotes lung adenocarcinoma metastasis

Abstract: Lung cancer is notorious for its ability to metastasize, but the pathways regulating lung cancer metastasis are largely unknown. An in vitro system designed to discover factors critical for lung cancer cell migration identified brain-derived neurotrophic factor, which stimulates cell migration through activation of tropomyosinrelated kinase B (TrkB; also called NTRK2). Knockdown of TrkB in human lung cancer cell lines significantly decreased their migratory and metastatic ability in vitro and in vivo. In an au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 39 publications
3
46
0
Order By: Relevance
“…BDNF/TrkB overexpression (Table i) confers a migratory phenotype to tumor cells and primes cancer cells to resist substantial genotoxic stressors, most of which are front-line chemotherapies (4-6). BDNF-mediated activation of TrkB also results in RAs activation (7), in turn accelerating cell-cycle progression and presumably contributing to poor prognosis of patients with cancers dependent on the BDNF signaling pathway (8,9). BDNF and Trkb overexpression has also been shown to contribute to oncogenesis of aggressive neuroblastoma cells (10) and to post-chemotherapeutic recurrence of highly aggressive breast cancer stem cells (11), demonstrating that this signaling pathway seems to be ubiquitous in the progression of multiple cancers and dynamically regulates several aspects of tumor cell physiology.…”
Section: Abstract Neurotrophins Are a Family Of Growth Factors That mentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF/TrkB overexpression (Table i) confers a migratory phenotype to tumor cells and primes cancer cells to resist substantial genotoxic stressors, most of which are front-line chemotherapies (4-6). BDNF-mediated activation of TrkB also results in RAs activation (7), in turn accelerating cell-cycle progression and presumably contributing to poor prognosis of patients with cancers dependent on the BDNF signaling pathway (8,9). BDNF and Trkb overexpression has also been shown to contribute to oncogenesis of aggressive neuroblastoma cells (10) and to post-chemotherapeutic recurrence of highly aggressive breast cancer stem cells (11), demonstrating that this signaling pathway seems to be ubiquitous in the progression of multiple cancers and dynamically regulates several aspects of tumor cell physiology.…”
Section: Abstract Neurotrophins Are a Family Of Growth Factors That mentioning
confidence: 99%
“…What is of considerable interest is that the BDNF/TrkB pathway has been shown to mediate the resistance to anoikis of multiple cancers (9,18,(25)(26)(27)(28)(29). it was shown that in multiple cancers, metastatic tumor cells have up-regulated TrkB and BDNF compared to tumor cells that did not metastasize (18,26,29).…”
Section: Role In Epithelial To Mesenchymal Transition and Anoikismentioning
confidence: 99%
“…TrkB overexpression participates in tumorigenesis through ERK and Akt pathway activation. This enhances the maintenance of brain tumor-initiating cells (BTICs) and promotes lung adenocarcinoma metastasis formation [30, 31]. Similarly, p75NR promotes survival and proliferation of BTICs and this effect requires proper p75NR cleavage by α- and γ-secretases [32].…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…In lung adenocarcinoma, EGFR is overexpressed in more than 39% and has emerged as a leading target for the treatment of patients with adenocarcinoma (10)(11)(12). Some TKIs, like gefitinib, significantly improved survival and prognosis of patients with lung adenocarcinoma, while some patients acquired resistance after initial response to TKIs or even had intrinsic resistance without EGFR mutations (13).…”
Section: Introductionmentioning
confidence: 99%